Nifuroxazide Mitigates Angiogenesis in Ehlrich’s Solid Carcinoma: Molecular Docking, Bioinformatic and Experimental Studies on Inhibition of Il-6/Jak2/Stat3 Signaling - Mohamed El-Sherbiny; Rehab M. El-Sayed; Mohamed A. Helal; Afaf T. Ibrahiem; Hoda S. Elmahdi; Mohamed Ahmed Eladl; Shymaa E. Bilay; Asma M. Alshahrani; Mona K. Tawfik; Ziad E. Hamed; Amany O. Mohamed; Sawsan A. Zaitone (Molecules, 2021)
Nifuroxazide is an antidiarrheal medication that has promising anticancer activity against diverse types of tumors. The present study tested the anticancer activity of nifuroxazide against Ehrlich’s mammary carcinoma grown in vivo. Furthermore, we investigated the effect of nifuroxazide on IL-6/jak2/STAT3 signaling and the possible impact on tumor angiogenesis. The biological study was supported by molecular docking and bioinformatic predictions for the possible effect of nifuroxazide on this signaling pathway. Female albino mice were injected with Ehrlich carcinoma cells to produce Ehrlich’s solid tumors (ESTs). The experimental groups were as follows: EST control, EST + nifuroxazide (5 mg/kg), and EST + nifuroxazide (10 mg/kg). Nifuroxazide was found to reduce tumor masses (730.83 ± 73.19 and 381.42 ± 109.69 mg vs. 1099.5 ± 310.83) and lessen tumor pathologies. Furthermore, nifuroxazide downregulated IL-6, TNF-α, NFk-β, angiostatin, and Jak2 proteins, and it also reduced tumoral VEGF, as indicated by ELISA and immunohistochemical analysis. Furthermore, nifuroxazide dose-dependently downregulated STAT3 phosphorylation (60% and 30% reductions, respectively). Collectively, the current experiment shed light on the antitumor activity of nifuroxazide against mammary solid carcinoma grown in vivo. The antitumor activity was at least partly mediated by inhibition of IL-6/Jak2/STAT3 signaling that affected angiogenesis (low VEGF and high angiostatin) in the EST. Therefore, nifuroxazide might be a promising antitumor medication if appropriate human studies will be conducted.